Ketamine Cystitis Following Ketamine Therapy for Treatment Resistant Depression – Case Report - Minna Chang; Allan Young; Mario Juruena (BJPsych Open)
Aims: Ketamine is a novel and exciting putative antidepressant medication for patients with treatment-resistant depression. A complication commonly seen in frequent and heavy recreational use of ketamine is ulcerative cystitis, which presents with lower urinary tract symptoms (LUTS) and upper renal tract damage and can be seen in over 25% of regular users.